Substantia nigra alterations in mice modeling Parkinson’s disease - I. N. Rozhkova; S. V. Okotrub; E. Yu. Brusentsev; T. A. Rakhmanova; D. A. Lebedeva; V. S. Kozeneva; N. A. Shavshaeva; N. V. Khotskin; S. Ya. Amstislavsky (Вавиловский журнал генетики и селекции)
Parkinson’s disease (PD) is an age-related neurodegenerative pathology of the central nervous system. The well-known abnormalities characteristic of PD are dysfunctions in the nigrostriatal system including the substantia nigra of the midbrain and the striatum. Moreover, in PD persons, alpha-synucleinopathy is associated with abnormalities in the dopaminergic brain system. To study the mechanisms of this pathology, genetic models in mice have been designed. Transgenic mice of the B6.Cg-Tg(Prnp-SNCA*A53T)23Mkle/J strain (referred to as B6.Cg-Tg further in the text) possess the A53T mutation in the human alpha-synuclein SNCA gene. The density of neurons in the prefrontal cortex, hippocampus, substantia nigra and striatum in B6.Cg-Tg mice was assessed in our previous work, but the dopaminergic system was not studied there, although it plays a key role in the development of PD. The aim of the current study was to investigate motor coordination and body balance, as well as dopaminergic neuronal density and alpha-synuclein accumulation in the substantia nigra in male B6.Cg-Tg mice at the age of six months. Wild-type mice of the same sex and age, siblings of the B6.Cg-Tg mice from the same litters, lacking the SNCA gene with the A53T mutation, but expressing murine alpha-synuclein, were used as controls (referred to as the wild type further in the text). Motor coordination and body balance were assessed with the rota-rod test; the density of dopaminergic neurons and accumulation of alpha-synuclein in the substantia nigra were evaluated by the immunohistochemical method. There was no difference between B6.Cg-Tg mice and WT siblings in motor coordination and body balance. However, accumulation of alpha-synuclein and a decrease in the number of dopaminergic neurons in the substantia nigra were found in the B6.Cg-Tg mouse strain. Thus, the mice of the B6.Cg-Tg strain at the age of six months have some symptoms of the onset of PD, such as the accumulation of mutant alpha-synuclein and a decrease in the number of dopaminergic neurons in the substantia nigra. Taken together, the results obtained in our work qualify the B6.Cg-Tg strain as a pertinent model for studying the early stage of human PD already at the age of six months.